Translating tolerogenic therapies to the clinic – where do we stand? - Issa, Fadi; Wood, Kathryn J. (Frontiers in Immunology, 2012)
Manipulation of the immune system to prevent the development of a specific immune response is an ideal strategy to improve outcomes after transplantation. A number of experimental techniques exploiting central and peripheral tolerance mechanisms have demonstrated success, leading to the first early phase clinical trials for tolerance induction. The first major strategy centres on the facilitation of donor-cell mixed chimerism in the transplant recipient with the use of bone marrow or haematopoietic stem cell transplantation. The second strategy, utilising peripheral regulatory mechanisms, focuses on cellular therapy with regulatory T cells. This review examines the key studies and novel research directions in the field of immunological tolerance.